From a Mustard Seed: Enlivening Worship and Music in the Small Church - Epperly, Bruce G.; Hollinger, Daryl (Rowman & Littlefield Publishers, 2010)
Small congregations can have beautiful worship! In From a Mustard Seed: Enlivening Worship and Music in the Small Church, an experienced pastor-professor and an experienced church musician provide a model for faithful and excellent worship in congregations that average 75 or fewer people in weekly worship. While the limitations of small congregations are obvious to their members and leaders, the possibilities for creative music and worship are often greater than we can imagine. Epperly and Hollinger integrate theology, spiritual formation, and practical guidance for nurturing diverse, inspirational, and transforming worship in small congregations. Grounded in a solid theology of worship, they provide tried-and-true approaches to congregational music and singing, worship planning, liturgies that transform, and healthy partnerships between pastors and church musicians. God is present in small congregations, and the authors help pastors, church musicians, and active laypersons awaken to God's activity in every aspect of worship and music. They illuminate possibilities for opening to God in worship and music through their own stories, the stories of congregations and their pastors, practical counsel, spiritual practices, and theological reflection.